ERROR ANALYSIS OF CONDITIONAL SENTENCES - Kristina, Wilna; Rufinus, Albert; Maiza, Masfa (English Language Education Study Program, 2020)
Making mistakes when using conditional sentences is common for foreign language learners. Errors in this study are in accordance with the error classification surface strategy taxonomy, namely omission, addition, misform ation and misordering. The purposes of this study are to identify and to classify the types of error and to find the factors causing errors in the use of conditional sentences. The research method used is descriptive qualitative research method that is a case study with taxonomic analysis. Data collection techniques were carried out using test and interview. The research subject was third semester students of the English Language Education Study Program 2018/2019 of Pamane Talino College of Education in Landak Regency, West Kalimantan. The results show that 30.27% of students make omission errors, 21.11% addition errors, 34.86% misformation errors and 13.76% misordering errors. The factors that cause errors are found from the system's own target language (intralingual). The main error factors classified as intralingual errors in this study are: incomplete knowledge in verb forms, incomplete application of rules and false concept hypothesis.